ALIH KODE DALAM PENGENALAN BAHASA INGGRIS ANAK USIA DINI - Purandina, I Putu Yoga (Pratama Widya: Jurnal Pendidikan Anak Usia Dini, 2022)
This study aims to determine the use of code-switching in the introduction of English in TK and KB Swasti Karya, Megati Village, Tabanan Regency, Bali. The factors causing the use of code-switching are also one of the aim in this research. This research is a qualitative descriptive study in which the researcher analyzes the speech of teachers and children in the introduction to English class in TK and KB Swasti Karya. There are 4 teachers and 59 children are divided into TK and KB groups. The instrument used is a list of observation guidelines, interviews, and documentation. An in-depth analysis was carried out on the utterances using the code-switching theory by Poplack (2001). The results of this study found 18 utterances indicated code-switching. A total of 7 utterances are categorized in insertion (intra-sentential code-switching), and 11 utterances are categorized in alternation (inter-sentential code-switching). Meanwhile, the category of congruent lexicalization was not found in this study. Then the factors that influence the use of this code-switching are (1) to convey meaning effectively when facing difficulties in conveying meaning, (2) making communication more inclusive or closer to certain students/groups/etc, (3) improve students' understanding when they have not achieved the learning objectives, (4) to convey meaning or understanding contextually, (5) for meaning or understanding, (6) helping to help learners of English as a Foreign Language for bilingual children.